Exploring the Levels of Self-Efficacy in Microteaching Among Pre-Service Teachers - Siboro, Efrika; Febrianti, Dian; Rufinus, Albert; Kurniawan, Trio; Tawarik, Oxtapianus; Upa, Yunika (Universitas Pahlawan Tuanku Tambusai, 2026)
This study examines the self-efficacy levels of pre-service teachers in the dimensions of magnitude, strength, and generality during microteaching sessions. A descriptive quantitative survey design was employed, with data collected from 28 participants in the English Education Study Program at Universitas Katolik Santo Agustinus Hippo, selected through purposive sampling. A Likert-scale questionnaire and interviews were implemented to assess self-efficacy levels and identify the most dominant dimension. The data were analyzed using mean scores for each dimension of self-efficacy. Results showed high self-efficacy across all dimensions, with the strength dimension being the most dominant (mean = 2.828). Participants demonstrated high self-efficacy in handling complex tasks, managing disruptions, and applying their skills in diverse teaching contexts. However, some participants reported lower self-efficacy, particularly in managing disruptions and addressing diverse student needs.